Поліпшення результатів хірургічного лікування гнійно-некротичних форм синдрому діабетичної стопи - Ксенофонтов, С. С.; Білозерцев, О. М.; Башмаков, М. М.; Гудинов, І. Д. (Clinical Endocrinology and Endocrine Surgery, 2009)
In the article 132 patients with the purative-necrotic forms of syndrome of diabetic foot were investigated. A troubleshooting routine and principles of treatment is shown, including surgical organ-preserving tactics; radical abolishing of purative and/or necrotic defects; valuable staging necrectomies; maximally possible maintenances of supporting and springing function of foot; as possible early closing of the surgically treated wound. In a dynamics marked the reliable decline of frequency of large amputations of extremities from 31% in 1999 to 14,2% in 2007, diminishing of lethality to 4,6%. Results, obtained in our opinion, satisfy of expedience and justified of such medical measures and induce to subsequent perfection of all links of complex decision of problem of syndrome of diabetic foot.